PENGARUH RASIO CAMEL DAN UKURAN BANK TERHADAP PREDIKSI KONDISI BERMASALAH PADA SEKTOR PERBANKAN (Studi Pada Perusahaan Perbankan yang Terdaftar Di Bursa Efek Indonesia Tahun 2007 – 2011 ) - Rizky Bestari, Adhistya; Rohman, Abdul (Diponegoro Journal of Accounting, 2013)
This research aims to analyze the effect of the CAMEL Ratio and Bank Size for thep trouble bank prediction that use ratio such as Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Net Interest Margin (NIM), Return On Asset (ROA), Operating Expense to Operating Income (BOPO), Loan to Deposite Ratio (LDR) and Bank size. The data used from annual published financial statement of Commercial bank period 2007-2011. The population in this study are 35 commercial bank, after pass the purposive samplig there are 19 bank samples. The sample of research was devided in two categoriest bank with no problem are 16 bank and 3 bank in trouble. Methode of analyze used to test the hypothesis of the research is logistic regression. The result of the research show that NIM is significant effect of the trouble bank prediction and Bank size is significant effect of the trouble bank prediction. Other variables such as CAR, NPL, ROA, BOPO,and LDR do not have significant effect the trouble bank prediction